2013
DOI: 10.1002/pssa.201330199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing and MgO thickness on perpendicular magnetic anisotropy in Pt/Co2FeAl0.5Si0.5/MgO/Pt multilayers

Abstract: Phone/Fax: þ86 10 62333209Magnetic properties have been studied for Ta/Pt/Co 2 FeAl 0.5 Si 0.5 (CFAS)/MgO/Pt multilayers to investigate the effects of annealing and MgO thickness on perpendicular magnetic anisotropy (PMA). We show that PMA is very sensitive to the annealing conditions and MgO thickness. Strong PMA with high remanence ratio can be achieved after annealing at 300 8C for just 10 min. The thickness of CFAS (t CFAS ) with PMA is strongly dependent on the MgO thickness (t MgO ). A large t CFAS with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It is similar to the Pt/Co (or CoFeB)/MgO structure in which there is also a transition from IMA to PMA after annealing due to the oxidation of Co (or CoFeB). The PMA of Pt (5 nm)/CFAS (1.5 nm)/MAO (0.9 nm) is stable even after annealing at 400 °C, which is comparable to that of Pt/CFAS/MgO structure . Further increasing T a to 450 °C, the easy magnetic axis gets back to in‐plane again, and the PMA disappears.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…It is similar to the Pt/Co (or CoFeB)/MgO structure in which there is also a transition from IMA to PMA after annealing due to the oxidation of Co (or CoFeB). The PMA of Pt (5 nm)/CFAS (1.5 nm)/MAO (0.9 nm) is stable even after annealing at 400 °C, which is comparable to that of Pt/CFAS/MgO structure . Further increasing T a to 450 °C, the easy magnetic axis gets back to in‐plane again, and the PMA disappears.…”
Section: Resultsmentioning
confidence: 76%
“…The annealing procedure includes three steps as follow: firstly, the center area of quartz‐glass tube was heated to given temperatures in vacuum with a heating rate of 10 °C min −1 ; secondly, the samples were rapidly pushed into the center of quartz‐glass tube and annealed for 30 min; finally, the samples were pulled out of the heated area and naturally cooled to room temperature in vacuum without external magnetic field. The crystal structure of CFAS has been studied by grazing incidence X‐ray diffraction under the same fabrication conditions in our previous work . It was demonstrated that the as‐deposited CFAS films are crystallized in disordered A2 phase.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…IPA and PMA originate from the shape anisotropy and interface anisotropy of the films. Hence, recent research has been mainly concentrated on fabricating multilayer films with PMA property . In this study, we have put effort to achieve the strong PMA property of CFA film on MgO buffer layer by varying the MgO film thickness and annealing temperature for p‐MTJs‐based spintronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a promising oxide layer of MgO has a good lattice match with Co 2 FeAl (CFA) films and the interface between CFA and MgO could strongly induce the PMA property. The presence of PMA is widely originated from the Co/Fe‐3d and O‐2p orbitals hybridization at FM/(MgO or MgAl 2 O 4 ) interface with suitable buffer layers . Recently, CFA is found to display the PMA property with different buffer layer systems such as Pt/CFA/MgO, Cr/CFA/MgO, Ta/CFA/MgO, and Ta/Pd/CFA/Ta layers .…”
Section: Introductionmentioning
confidence: 99%